Vasoplegic syndrome after off pump coronary artery bypass grafting surgery - Vaidyanathan, Swaminathan; Chidambaram, Kumar; Mohanraj, Anbarasu (International Journal of Research in Medical Sciences, 2017)
We report a case of 48-years-old man who developed nor-epinephrine resistant vasoplegic syndrome after elective off pump coronary artery bypass grafting surgery. The failure of norepinephrine to improve the patients’ hemodynamics promted us to start treatment with vasopressin. Within an hour, the hemodynamics begin to improve. After 4 hours, patient was stable enough to be weaned from vasopressin, extubated at the end of 24 hrs and shifted to ward at the end of 48 hours. Vasoplegic syndrome can occur commonly after cardiopulmonary bypass and incidence can go up to 10%. This case was reported to insist upon the fact that vasoplegic syndrome can occur even after off pump surgeries. Herein we discuss the aetiology, risk factors, pathophysiology and prophylactic measures to be taken, for the prevention of vasoplegic syndrome.